1998
DOI: 10.1177/004051759806800801
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Processing of Fine Merino Lamb's Wool

Abstract: Literature pertinent to fiber properties and handle of fine Merino lamb's and fleece wool is critically discussed. The softness of handle of fine Merino wool varies inversely with loose fiber resistance to compression. This complex raw wool parameter has geometric and mechanical attributes. Fiber bending and torsional rigidity are important mechanical factors that depend on mean fiber diameter, cross-sectional shape, and Young's modulus. Crimp frequency, amplitude, and form are equally important geometric fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…CURRENT WOOLEN SYSTEM RESEARCH More recent research reported in detail elsewhere [9,10,11,12] covers the conversion of several batches of lamb's and nonlamb's wool with mean fiber diameters of 16.4-19.4 Am, staple crimp of 4.9-8.4/cm, and resistance to compression of 6.9-15.0 kPa. R144/2 tex, S270/ Z 120 tpm yarns were knitted to single jersey fabric using a 10 gauge circular machine and milled to a finished weight of 400 g -m -2.…”
Section: Introductionmentioning
confidence: 99%
“…CURRENT WOOLEN SYSTEM RESEARCH More recent research reported in detail elsewhere [9,10,11,12] covers the conversion of several batches of lamb's and nonlamb's wool with mean fiber diameters of 16.4-19.4 Am, staple crimp of 4.9-8.4/cm, and resistance to compression of 6.9-15.0 kPa. R144/2 tex, S270/ Z 120 tpm yarns were knitted to single jersey fabric using a 10 gauge circular machine and milled to a finished weight of 400 g -m -2.…”
Section: Introductionmentioning
confidence: 99%
“…The handle of superfine wool is determined largely by the average diameter. However, the fiber diameter changes throughout the growth period of the superfine wool [2,3]. Therefore, many researchers have investigated this problem.…”
mentioning
confidence: 99%
“…Methods used to sample and test both individual fleeces and bulk quantities of wool included both standard and nonstandard approaches [8]. We modified a CSIRO Sonic B wool fineness tester [ 2 ] to display digital millivoltage rather than that of the normal analog meter.…”
mentioning
confidence: 99%
“…We devised a sampling protocol with which to randomly select representative staples from both individual fleeces and bulk wool lots [ 8 ] . We measured the mean staple length and crimp frequency and variation in both using &dquo;Style-MARK 3,&dquo; a CSIRO experimental instrument [ 3 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation